Chiral Recognition of Lysine by Cyclodextrin Intercalated Layered Double Hydroxides - Lei Liu, Xiao (Asian Journal of Chemistry, 2013)
The chiral sorption of racemic lysine by carboxymethyl-a-cyclodextrin intercalated layered double hydroxides has been studied. It was found that L-lysine was preferentially adsorbed by carboxymethyl-a-cyclodextrin intercalated layered double hydroxides. Furthermore, the intraparticle diffusion model was successfully validated in this work. Intraparticle effective diffusivities (Deff) of lysine in carboxymethyl-a-cyclodextrin intercalated layered double hydroxides macroparticle were determined from the homogeneous Fickian diffusion model. Moreover, the crystallites diffusivity (Dc) and pore diffusivity (Dp) for the parallel diffusion model were determined.